Plasma NT-proBNP and pulmonary to systemic blood flow ratio in congenital heart defects with left-to-right shunts - Eko Kristanto Kunta Adjie; Ni Putu Veny Kartika Yantie; Made Gede Dwi Lingga Utama; Eka Gunawijaya; Ketut Ariawati; Ida Bagus Subanada; Anak Agung Ngurah Ketut Putra Widnyana (Paediatrica Indonesiana, 2020)
Background Cardiac left-to-right shunts changes to the pulmonary-to-systemic blood flow ratio (Qp/Qs ratio). This ratio can be used to monitor the hemodynamics of the heart. Left-to right-shunts cause the release of amino terminal proB-ty natriuretic peptide (NT-proBNP) that can be utilized as a specific marker for the presence of heart failure in children with congenital heart defects (CHDs). Early intervention such as defect closure in CHD is important to prevent heart failure.